Dynamic Stability and Reactive Power Control Using Dandelion-Optimized Cascaded Fractional Order Tilt Controller in Renewable Energy Systems - G. M. Sachin; Abhik Banerjee; S. N. Deepa (IEEE Access)
Wind energy is recognized as a key sustainable resource in the renewable energy industry. Reactive power imbalance arises from load disturbances and fluctuations in wind power, directly impacting the stability of hybrid wind-integrated power systems. These imbalances result in voltage deviations within the power systems. Dynamic voltage stability (DVS) and reactive power compensation (RPC) in standalone wind-diesel hybrid power systems (SWDHPS) may be achieved by installing suitable compensating devices with novel control strategies. This paper proposes a novel cascaded fractional-order PI-tilt integral second-order double-derivative controller (FOPI-TIDD2) integrated with STATCOM for DVS enhancement and RPC in SWDHPS. The tunable parameters of the proposed controller are optimized using an improved dandelion optimization (DO) algorithm. The controller’s performance is evaluated by comparing its dynamic voltage characteristics with those of traditional controllers. Similarly, the effectiveness of the DO algorithm is validated through a comparative analysis of dynamic voltage and convergence characteristics with those of traditional algorithms. Furthermore, the robustness of the proposed controller is assessed through sensitivity analysis under different loading conditions. The proposed approach is implemented and validated through simulations in MATLAB/Simulink and further verified via real-time implementation on the OPAL-RT platform. The results demonstrate that the DO-tuned FOPI-TIDD2 controller integrated with STATCOM significantly enhances RPC and DVS in SWDHPS.